Arte, Censura e Soft Power na China Contemporânea - Chen, Cristina Choung [UNIFESP] (2019)
This paper discusses the relationship between Soft Power and governmental censorship in cultural management practices within mainland China, specifically in the field of visual arts. According to Joseph Nye Jr., creator of the term Soft Power, China emerges in the 21st century as a power to challenge American hegemony in economic and political terms, but the moral values presented by the Government, as well as the representation of Chinese culture in the global imagination, seem to precluding the public’s voluntary co-optation to a positive perception of the country. In this context, censorship is cited as the main obstacle to the creation of Soft Power. The research proposes to analyze the censor format within the artistic sphere, to reflect on the contemporary Chinese reality and to question the way such elements are articulated for the formation of individual expression within the global cultural scenario.